Key Determinants in The Preservation of Bamboo Weaving in Mekarsari Village, Selaawi Subdistrict, Garut Regency - Rawati, Fitrin; Purnamasari, Imas (Jurnal Wacana Ekonomi, 2025)
The objective of this study is to identify and analyze the determinants, particularly the most dominant, in the preservation of bamboo weaving in Mekarsari Village, Selaawi Subdistrict. The research employs an exploratory factor analysis method. Data were collected through questionnaires administered to 112 bamboo weaving artisans in Mekarsari Village, Selaawi Subdistrict. Upon gathering the responses, validity, reliability, and exploratory factor analysis were conducted. The study’s findings revealed seven key determinants in the preservation of bamboo weaving in Mekarsari Village, Selaawi Subdistrict: Factor 1 (Cultural and Family Factors), Factor 2 (Economic Sustainability of Bamboo Weaving), Factor 3 (Market and Raw Material Stability), Factor 4 (Leisure Utilization and Cultural Relevance), Factor 5 (Innovation and Government Support), Factor 6 (Traditional Skills and Product Durability), and Factor 7 (Product Uniqueness). The most dominant determinant in the preservation of bamboo weaving in Mekarsari Village, Selaawi Subdistrict, is Factor 1 (Cultural and Family Factors).